Comparison of modified two‐point dixon and chemical shift encoded MRI water‐fat separation methods for fetal fat quantification. Issue 1 (10th January 2018) - Giza, Stephanie A.; Miller, Michael R.; Parthasarathy, Prasiddha; de Vrijer, Barbra; McKenzie, Charles A.
Abstract : BACKGROUND: Fetal fat is indicative of the energy balance within the fetus, which may be disrupted in pregnancy complications such as fetal growth restriction, macrosomia, and gestational diabetes. Water‐fat separated MRI is a technique sensitive to tissue lipid content, measured as fat fraction (FF), and can be used to accurately measure fat volumes. Modified two‐point Dixon and chemical shift encoded MRI (CSE‐MRI) are water‐fat separated MRI techniques that could be applied to imaging of fetal fat. Modified two‐point Dixon has biases present that are corrected in CSE‐MRI which may contribute to differences in the fat measurements. PURPOSE: To compare the measurement of fetal fat volume and FF by modified two‐point Dixon and CSE‐MRI. STUDY TYPE: Cross‐sectional study for comparison of two MRI pulse sequences. POPULATION: Twenty‐one pregnant women with singleton pregnancies. FIELD STRENGTH/SEQUENCE: 1.5T, modified two‐point Dixon and CSE‐MRI. ASSESSMENT: Manual segmentation of total fetal fat volume and mean FF from modified 2‐point Dixon and CSE‐MRI FF images. STATISTICAL TESTS: Reliability was assessed by calculating the intraclass correlation coefficient (ICC). Agreement was assessed using a one‐sample t‐test on the fat measurements difference values (modified two‐point Dixon ‐ CSE‐MRI). The difference scores were tested against a value of 0, which would indicate that the measurements were identical. RESULTS: The fat volume and FF measured by modified two‐point Dixon and CSE‐MRI had excellent reliability, demonstrated by ICCs of 0.93 ( P < 0.001) and 0.90 ( P < 0.001), respectively. They were not in agreement, with CSE‐MRI giving mean fat volumes 180 mL greater and mean FF 3.0% smaller than modified two‐point Dixon. DATA CONCLUSION: The reliability between modified two‐point Dixon and CSE‐MRI indicates that either technique can be used to compare fetal fat measurements in different participants, but they are not in agreement possibly due to uncorrected biases in modified two‐point Dixon. Level of Evidence: 4 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2018.